Party reputations and policy priorities: how issue ownership shapes executive and legislative agendas - Green, J; Jennings, W (Cambridge University Press, 2017)
Election-oriented elites are expected to emphasize issues on which their party possesses ‘issue ownership’ during campaigns. This article extends those theories to the content of executive and legislative agendas. Arguing that executives have incentives to pursue their party’s owned issues in the legislature, it theorizes three conditions under which these incentives are constrained: when governments are responsive to issues prioritized by the public, when a party has a stronger electoral mandate and under divided government. The theory is tested using time-series analyses of policy agendas of US congressional statutes and State of the Union addresses (1947–2012) and UK acts of Parliament and the Queen’s Speech (1950–2010). The results offer support for the theory, and are particularly strong for the US State of the Union address, providing insights into institutional differences. The implications provide reassurance concerning the conditions under which governments focus attention only on their partisan issue priorities.